The Return of the Taliban Afghanistan After the Americans Left - Hassan Abbas (London Yale University Press, 2023)
BThe first account of the new Taliban-showing who they are, what they want, and how they differ from their predecessors/BBR / BR / Since the fall of Kabul in 2021, the Taliban have effective control of Afghanistan-a scenario few Western commentators anticipated. But after a twenty-year-long bitter war against the Republic of Afghanistan, reestablishing control is a complex procedure. What is the Taliban's strategy now that they've returned to power?BR / BR / In this groundbreaking new account, Hassan Abbas examines the resurgent Taliban as ruptures between moderates and the hardliners in power continue to widen. The group is now facing debilitating threats-from humanitarian crises to the Islamic State in Khorasan-but also engaging on the world stage, particularly with China and central Asian states. Making considered use of sources and contacts in the region, and offering profiles of major Taliban leaders, IReturn of the Taliban/I is the essential account of the movement as it develops and consolidates its grasp on Afghanistan.
Including Index and Bibliograpy
Keywords: History